A qualitative study of graduate student emotional and cognitive processing of unexpected (chance) events - Hope Ferguson; Elisabeth E. Schussler (PLoS ONE, 2025)
Research on graduate education often focuses on the expected challenges of graduate programs, such as proposal defenses, comprehensive exams, and mentoring relationships. However, less is known about how unexpected (chance) events may shape graduate student program experiences, including their impacts on career intentions. Prior research suggests that unexpected events introduce uncertainty and opportunities, however, the emotional and cognitive processes underlying these perceptions are unknown. This study explored how graduate students emotionally and cognitively processed a self-reported highly impactful chance event during their program. Specifically, this study asked 1) How did life science graduate students initially appraise and reappraise chance events? and 2) How did the narratives of chance event appraisals differ among participants who changed their career intentions versus those who did not? Using Appraisal Theory, we conducted thematic narrative analysis for the interviews with ten current life science graduate students. Five students had changed their career intentions since starting graduate school and five had not. These analyses revealed that themes of Initial Stressors, Initial Emotional Toll, and Growth were shared among participants, highlighting these as common processes related to unexpected events. However, the Help-Seeking, Self-Reliance, Realizations, and Resilience themes differed among those who had changed their career intentions or not. Those who had changed their career intentions often coped by using external support and prioritizing their mental well-being. Those who had not changed their career intentions coped via self-reliance, focusing on self-managing challenges and viewing chance events as opportunities to build new skill sets. This study demonstrated the utility of applying Appraisal Theory to graduate study, showcasing how appraisal and reappraisals of unexpected events may be related to career decision making. Implications include the need for effective coping strategies to navigate unexpected challenges and faculty and departmental support for career development.